Adoptive immunotherapy with interleukin-2 and lymphokine-activated killers in patients with malignant neoplasms of the female reproductive system (a review of literature) - A. N. Gritsai; D. A. Baranovsky; M. V. Kiselevsky; I. L. Gulyaeva (Опухоли женской репродуктивной системы)
The review highlights current approaches to adoptive immunotherapy in patients with malignant neoplasms of the female reproductive system.In spite of the obvious advances made by scientists of the world in treating malignant neoplasms, the existing treatment options remain insufficiently effective. To search for novel highly effective and safe treatments is an urgent problem of oncology. Adoptive immunotherapy is one of the priorities in this regard.